Democratic Republic of Congo : Health, Nutrition and Population, Country Status Report - World Bank (Washington, DC, 2012)
The objective of this report is to describe and analyze the health, nutrition, and population situation in Democratic Republic of Congo (DRC) in order to inform the Government's strategy development in the sector, particularly in the context of its Poverty Reduction Strategy Paper (PRSP). The report analyzes health, nutrition, and population outcomes and determinants, focusing on the Millennium Development Goals (MDGs) and the health situation of the poor. Health service utilization and i t s determinants are assessed, and the main features of the health system described. The policies and strategies of Government and external partners are discussed, with particular attention to the health care financing situation and its impact on the poor.